Scientific, Cultural and Religious Services of Bani Bagtakin or Arbil Atabaks (before 592-630AH 1145-1223AD). - Hasheminia, Seyyed Mohammadreza; Torbatinezhad, Behjat (Nur Science Institute, 2024)
Abstract Seljuks had a major role in political, racial, religious, economic, social, and cultural developments in Islamic lands under their territory. The Atabaki entity was introduced to Islam by Seljuk Turks. This study is to examine the scientific, cultural, and religious services of the Arbil Atabaks (Bani Bagtakin) government, which made their government last for about a century. According to the political, cultural, social, and military conditions and also the conflicts of local government in this period, many scholars and jurists were raised in the territory of Arbil Atabaks, and many books were written in a variety of fields. At this time many mosques, schools, orphanages, workhouses, hospitals, and monasteries were established, too. Mozaffar ad-Din Kokabori who was a famous ruler of this family took action for the welfare of the people, his actions included the improvement of roads, the establishment of security, the building of castles, and the repair of Bi’rmeimoun in (604 AH), which were very significant historically. In this period, the birthday of the Prophet Muhammad (PBUH) was celebrated for the first time in history. The Research Methodology of this study is Descriptive- Analytical and the data collection method is library-based. An attempt was made to examine the issue by means of relevant and main sources. Keywords: Cultural-Religious, Atabaks Territory, Seljuk Turks, Muzaffaruddin Kokabori, Bi’rmeimoun REFERENCE Ebrahim Hassan, Hassan, 1386. Political history of Islam. translated by Abul Qasem Payandeh, Alami Farhani, Tehran. Bosworth, Clifford Edmond, 1381, Islamic dynasties and a guide to Islamic chronology and genealogy, translated by Fereydoun Badraei, Islamic and Iran Research Center, Tehran. Abu Shameh, Abd al-Rahman, 1997, Al-Dhail Ali Al-Ruzateen (Translations of Men) by Ebrahim, Zaibaq, Beirut. Ibn Athir, Ezzuddin Abul Hasan Ali, 1415 AH 1995 AD, Al-Kamal by the efforts of Abul Fida Abd Allah Qazi, Beirut. Sabbat Ibn Jozi, Yusuf, 1371 AH, 1952 AD, Marah Al-Zaman, Hyderabad Deccan. Ibn Khalqan, Ahmad bin Muhammad, 1381, death of Al-Aiyan, Shuja Sanjari, translated by Fatemeh Madrasi, Tehran. Ibn Wasil, Muhammad bin Salem, 1395 AH 1975 AD, Mufaraj al-Karoob by Hasnain, Muhammad, Rabi, Cairo. Dhahabi, Muhammad bin Ahmad, 1948 AD, Al-Abar, with the efforts of Salahuddin Monjad, Kuwait. Ibn Ibri, 1986, Tarikh al-Zaman, translated by Ishaq, Ermela, Beirut. Naimi, Abd al-Qadri, 1410 A.H., al-Daras fi al-tarikh al-madaris, by Ebrahim Shams al-Din, Beirut Ibn Khalqan, 1964, Deaths, Ibn Shaddad, Yusef, Al-Nawad al-Sultaniyyah, with the efforts of Jamal al-Din Shiyal, Cairo. Ashraf al-Rasuli, Ismail, 1395 AH 1975 AD, Al-Asjad al-Masbuk, by the efforts of Shakir Mahmoud Abdul-Moneim, Baghdad, Beirut. Dhahabi, 1413 AH, Sira Alam al-Nabla, by the efforts of Shoaib Arnaut and Mohammad Naeem Argasousi, Beirut Sajjadi, Sadegh, 1383, Bani Bagtkin,